2022
DOI: 10.1016/j.tranon.2021.101307
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AURKA in treatment of peritoneal tumor dissemination in gastrointestinal cancer

Abstract: Intraperitoneal (i.p.) tumor dissemination and the consequent malignant ascites remain unpredictable and incurable in patients with gastrointestinal (GI) cancer, and practical advances in diagnosis and treatment are urgently needed in the clinical settings. Here, we explored tumor biological and immunological mechanisms underlying the i.p. tumor progression for establishing more effective treatments. We established mouse tumor ascites models that murine and human colorectal cancer cells were both i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…AURKA has been identified as a target gene for cancer treatment, and a small molecule that targets AURKA has been found [ 38 ]. Ozawa et al showed that targeting AURKA could be a promising strategy for improving clinical outcomes in the treatment of gastrointestinal cancer [ 39 ]. Zhang et al showed that MLN8237, an inhibitor of AURKA, efficiently reduced the proliferation and motility of pancreatic ductal adenocarcinoma cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…AURKA has been identified as a target gene for cancer treatment, and a small molecule that targets AURKA has been found [ 38 ]. Ozawa et al showed that targeting AURKA could be a promising strategy for improving clinical outcomes in the treatment of gastrointestinal cancer [ 39 ]. Zhang et al showed that MLN8237, an inhibitor of AURKA, efficiently reduced the proliferation and motility of pancreatic ductal adenocarcinoma cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein AURKA is a serine/threonine kinase that regulates mitosis by activating mitosis-related proteins. Ozawa H et al showed that the targeting of AURKA may improve the clinical outcome of gastrointestinal cancer (GI) [22]. Zhang et al showed that MLN8237, an inhibitor of Aurora kinase-A, e ciently reduced the proliferation and motility of pancreatic ductal adenocarcinoma (PDAC) cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PD1 is also expressed in Mø in the peritoneal cavity of mice and human. Ozawa et al reported that PD1 + TAMs with dysfunctional phagocytosis are expanded in the peritoneal cavity with disseminated tumor cells in mouse CRC ascites models and GC patients (189). The peritoneal tumor cells are polyploidy (giant with large nuclei) highly expressing aurora kinase A (AURKA) and GDF15 that is partly involved in the PD1 + TAM expansion.…”
Section: Pd1 + Myeloid Subsetsmentioning
confidence: 99%